2012
DOI: 10.1520/gtj20120099
|View full text |Cite
|
Sign up to set email alerts
|

Development of a Large-Scale Infiltration Column for Studying the Hydraulic Conductivity of Unsaturated Fouled Ballast

Abstract: In order to study the hydraulic behavior of fouled ballast, an infiltration column of 600 mm high and 300 mm in diameter was developed. Five TDR sensors and five tensiometers were installed at various levels, allowing the measurement of volumetric water content and matric suction, respectively. The material studied was fouled ballast that was formed in the railway track-bed by penetration of finegrained soil into the ballast. This material is characterized by a high contrast of size between the largest and the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(20 citation statements)
references
References 34 publications
0
20
0
Order By: Relevance
“…(Duong et al, 2013) a Bell (1992) b Banks et al (2013) c Banks (2012) d Selig & Waters (1994) From Smethurst et al, 2015). Note that the symbols mark the maximum extent of installation and that the tree location, form and height are not to scale.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…(Duong et al, 2013) a Bell (1992) b Banks et al (2013) c Banks (2012) d Selig & Waters (1994) From Smethurst et al, 2015). Note that the symbols mark the maximum extent of installation and that the tree location, form and height are not to scale.…”
Section: Discussionmentioning
confidence: 99%
“…The clay fill was assigned a lower air entry value and a curve of shallower gradient than the in situ London Clay, reflecting its greater specific volume and wider range of pore sizes, following Loveridge et al (2010) and Briggs et al (2013a). A SWRC for fouled ballast (given by Duong et al, 2013) was used to model the ash / ballast layer at the site.…”
Section: Materials Propertiesmentioning
confidence: 99%
See 1 more Smart Citation
“…( [7]) All sensors were checked and calibrated in laboratory before installation work. Calibration of TDR probes included the effects of temperature, soil type and soil unit mass upon the measured values ( [16,18,19,20,21,22,23]). The influence of temperature upon the measurement with strain gauges was also checked in laboratory and included into calibration.…”
Section: Figure 2 Grain Size Distributionmentioning
confidence: 99%
“…However, many studies have shown that hydraulic conductivities computed in the laboratory tend to have a smaller mean and a larger variance than conductivities observed in the field over larger scales (Chapuis et al, 2005;Clauser, 1992;Parker & Albrecht, 1987;Rovey & Niemann, 1998;Sobieraj, Elsenbeer, & Cameron, 2004;Yang et al, 2017). In any case, scale effects may vary according to measurements conditions, geological characteristics and the spatial correlation length of hydraulic conductivity in a specific site (Neuman, 1994; (Duong, Trinh, Cui, Tang, & Calon, 2013;Khan & Jury, 1990;Lai & Ren, 2007), resulting in a lack of knowledge that we hope to contribute to reduce.…”
Section: Introductionmentioning
confidence: 99%